The production scheduling using economic lot sizing approach at a pharmaceutical company. - Sumit, Gupta. (2008)
This thesis is the result of a three month internship at TCG Pharmaceuticals, Singapore. With the increasing demand of the products, the increased capital costs for putting capacity, it becomes very important for TCG to have an optimum scheduling With the worldwide initiative of lean manufacturing in TCG, it has implemented the TCG Production System which finds its roots in the famous Toyota Production System. The recognition of the importance of reducing the waste of inventory by TCG is the main motivational force for this internship. This thesis documents the total cost of holding inventory which is the sum of the set up costs and the inventory holding costs in the current scheduling scenario (Single Stage Two product system) and also analyzes the different scheduling options for their feasibilities. The main purpose of this thesis is to suggest the best scheduling option for the two product system in order to keep the total costs to a minimum possible level. The problem is solved using an Economic Lot Sizing approach and the different production lot sizes are compared. A comparison is made between the TCG’s planned production schedule and the production schedules developed based on the Economic Lot Sizing Model. The performance is measured in terms of the total effective cost of inventory.